The Cambridge introduction to narrative - Abbott, H. Porter (Cambridge ; New York : Cambridge University Press, 2008)
From the publisher. What is narrative? How does it work and how does it shape our lives and the texts we read? H. Porter Abbott emphasizes that narrative is found not just in literature, film, and theater, but everywhere in the ordinary course of people's lives. This widely used introduction, now thoroughly revised, is informed throughout by recent developments in the field and includes two new chapters. With its lucid exposition of concepts and suggestions for further reading, this book is not only an excellent introduction for courses focused on narrative but also an invaluable resource for students and scholars across a wide range of fields, including literature and drama, film and media, society and politics, journalism, autobiography, history, and still others throughout the arts, humanities, and social sciences.
1. Narrative and life : the universality of narrative ; Narrative and time ; Narrative perception -- 2. Defining narrative : The bare minimum ; Story and narrative discourse ; The mediation (construction) of story ; Constituent and supplementary events ; Narrativity -- 3. The borders of narrative : Framing narratives ; Paratexts ; The outer limits of narrative ; Hypertext narrative ; Is it narrative or is it life itself? -- 4. The rhetoric of narrative : The rhetoric of narrative ; Causation ; Normalization ; Masterplots ; Narrative rhetoric at work -- 5. Closure : Conflict: the agon ; Closure and endings ; Closure, suspense, and surprise ; Closure at the level of expectations; Closure at the level of questions ; The absence of closure -- 6. Narration : A few words on interpretation ; The narrator ; Does the narrator narrate everything? ; Voice ; Focalization ; Distance ; Reliability ; Free indirect style ; Narration on stage and screen -- 7. Interpreting narrative : The implied author ; Underreading ; Gaps ; Cruxes ; Repetition: themes and motifs -- 8. Three ways to interpret narrative : The question of wholeness in narrative ; Intentional readings ; Symptomatic readings ; Adaptive readings -- 9. Adaptation across media : Adaptation as creative destruction ; Duration and pace ; Character; Figurative language ; Gaps ; Focalization ; Constraints of the marketplace -- 10. Character and self in narrative : Character vs. action ; Flat and round characters ; Can characters be real? ; Types ; Autobiography ; Life writing as performative -- 11. Narrative and truth : Fiction and nonfiction ; How do we know if it's fiction or nonfiction ; Historical fact in fiction ; The truth of fiction -- 12. Narrative worlds : Narrative space ; The mind of the storyworld ; Multiple worlds: forking-path narratives ; Multiple worlds: narrative metalepsis -- 13. Narrative contestation : A contest of narratives ; A narrative lattice-work ; Shadow stories ; Motivation and personality ; Masterplots and types ; Revising cultural masterplots ; Battling narratives are everywhere -- 14. Narrative negotiation : Narrative negotiation ; Critical reading as narrative negotiation ; Closure, one more time ; The end of closure?
Includes bibliographical references (p. 223-227) and indexes.
Keywords: Narration (Rhetoric); Fiction -- Technique